The URL1–ROC5–TPL2 transcriptional repressor complex represses the ACL1 gene to modulate leaf rolling in rice. Issue 4 (13th January 2021) - Fang, Jingjing; Guo, Tingting; Xie, Zhiwei; Chun, Yan; Zhao, Jinfeng; Peng, Lixiang; Zafar, Syed Adeel; Yuan, Shoujiang; Xiao, Langtao; Li, Xueyong
Abstract: Moderate leaf rolling is beneficial for leaf erectness and compact plant architecture. However, our understanding regarding the molecular mechanisms of leaf rolling is still limited. Here, we characterized a semi-dominant rice ( Oryza sativa L.) mutant upward rolled leaf 1 ( Url1 ) showing adaxially rolled leaves due to a decrease in the number and size of bulliform cells. Map-based cloning revealed that URL1 encodes the homeodomain-leucine zipper (HD-Zip) IV family member RICE OUTERMOST CELL-SPECIFIC 8 (ROC8). A single-base substitution in one of the two conserved complementary motifs unique to the 3′-untranslated region of this family enhanced URL1 mRNA stability and abundance in the Url1 mutant. URL1 (UPWARD ROLLED LEAF1) contains an ethylene-responsive element binding factor-associated amphiphilic repression motif and functions as a transcriptional repressor via interaction with the TOPLESS co-repressor OsTPL2. Rather than homodimerizing, URL1 heterodimerizes with another HD-ZIP IV member ROC5. URL1 could bind directly to the promoter and suppress the expression of abaxially curled leaf 1 ( ACL1 ), a positive regulator of bulliform cell development. Knockout of OsTPL2 or ROC5 or overexpression of ACL1 in the Url1 mutant partially suppressed the leaf-rolling phenotype. Our results reveal a regulatory network whereby a transcriptional repression complex composed of URL1, ROC5, and the transcriptional corepressor TPL2 suppresses the expression of the ACL1 gene, thus modulating bulliform cell development and leaf rolling in rice. Abstract : A transcriptional repression complex suppresses the expression of a positive regulator of bulliform cell development, thus modulating bulliform cell development and leaf rolling in rice.